2011
DOI: 10.12782/specdiv.16.49
|View full text |Cite
|
Sign up to set email alerts
|

First Report of an Interstitial Semicytherura (Crustacea: Ostracoda: Cytheruridae: Cytherurinae) : a New Species from Central Japan

Abstract: A new species of ostracod, Senitqytherura scrgittijbrmis sp. nov., is described from a sandy beach in Shizueka Prefecture, centrai Japan. It lives in pore-waters of marine sandy sedirnents and is eeologically associated with other interstitial ostracods (e,g., Parmpolycope and Microloxoconcha). Semiqytherura sagittijbrmis is one of the smallest species in the genus Semicytherura, and its carapace size is comparable witih those of some large interstitial ostracods. This fact suggests that a small carapace is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Like other interstitial animals, these ostracods often show specialized morphological characters (Hartmann, ; Maddocks, ; Gottwald, ; Higashi & Tsukagoshi, ), e.g. they are much smaller than their surface‐dwelling relatives (Danielopol & Bonaduce, ; Yamada & Tanaka, ) and have reduced or absent eyes (Kaji & Tsukagoshi, ). Reduction of body size often results in convergent evolution of many characters both of the carapace and soft parts, and therefore it is sometimes hard to reveal the true phylogenetic relationships amongst closely related taxa based on morphological characters alone (Gottwald, ).…”
Section: Introductionmentioning
confidence: 99%
“…Like other interstitial animals, these ostracods often show specialized morphological characters (Hartmann, ; Maddocks, ; Gottwald, ; Higashi & Tsukagoshi, ), e.g. they are much smaller than their surface‐dwelling relatives (Danielopol & Bonaduce, ; Yamada & Tanaka, ) and have reduced or absent eyes (Kaji & Tsukagoshi, ). Reduction of body size often results in convergent evolution of many characters both of the carapace and soft parts, and therefore it is sometimes hard to reveal the true phylogenetic relationships amongst closely related taxa based on morphological characters alone (Gottwald, ).…”
Section: Introductionmentioning
confidence: 99%
“…This new Semicytherura species is the twenty-second species reported from the area. Yamada and Tanaka (2011) reported Semicytherura sagittiformis as the first interstitial Semicytherura species from Japan. Besides the small carapace size, both carapace and appendage morphology of S. sagittiformis resembles that of other, non-interstitial Semicytherura species.…”
Section: Taxonomymentioning
confidence: 99%
“…More than 30 species of the genus Semicytherura Wanger, 1957 including both living and fossil specimens, have been reported from Japan and its adjacent areas (Yamada and Tsukagoshi 2010). Moreover, Tanaka (2011, 2013) reported three interstitial species, i.e., S. mukaishimensis Okubo, 1980, S. sagittiformis Yamada and Tanaka, 2011, and S. uzushio Yamada and Tanaka, 2013. Yamada and Tanaka (2011 emphasized the importance of small carapace size in the genus Semicytherura for adaptation to the interstitial environment, and suggested that S. hanaii Ishizaki, 1981, S. okinawaensis Nohara, 1987, S. polygonoreticulata Ishizaki and Kato, 1976, S. ryukyuensis Nohara, 1987, S. sabula Frydl, 1982 (Hanai, 1957), and S. yajimae Published online 1 January 2020 DOI: 10.12782/specdiv.25.1 Ikeya and Zhou, 1992 would be interstitial species based on their small carapace size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interstitial environment can be regarded as a cryptic habitat, which is dark, has restricted spaces, and has a three‐dimensional, maze‐like structure. Most marine interstitial ostracods are characterized by being much smaller than surface‐dwelling species (Hartmann, ; Maddocks, ; Yamada & Tanaka, ), and a reduced or absent naupliar eye (Hartmann, ; Kaji & Tsukagoshi, ). All parapolycopid species exhibit some characteristics of interstitial species: small body size (0.2–0.4 mm in adult) and lack of eyes and a frontal organ (which has been suggested to be a photoreceptive structure: Müller, ; Hartmann, ).…”
Section: Introductionmentioning
confidence: 99%